The "conquest" of historical space in the 21st century Russia: negative historical identity? - Aurimas Švedas (Lietuvos Istorijos Studijos)
The radical social and political changes experienced by the societies of the post-Soviet space determine the transformations in their sociocultural mentality and create new forms of relation with the past. The construction of a new historical identity, which now proceeds in contemporary Russia, can be considered as a typical process for the post-Soviet country, the particularity of which is created by several factors: traumatic experience and the particularities of sociopolitical life in a country that suffers transformation.